2009
DOI: 10.1186/1748-717x-4-40
|View full text |Cite
|
Sign up to set email alerts
|

Patient information in radiation oncology: a cross-sectional pilot study using the EORTC QLQ-INFO26 module

Abstract: Background: The availability of alternative sources of information, e. g. the internet, may influence the quantity and quality of information cancer patients receive regarding their disease and treatment. The purpose of the present study was to assess perception of information in cancer patients during radiotherapy as well as media preferences and specifically the utilization of the internet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 23 publications
5
28
0
4
Order By: Relevance
“…Although some questions were answered satisfactorily, showing scores far superior to the average, it was observed that 89% of the sample indicates the desire to receive more overall information. This finding is very close to the results presented in other studies, (12)(13)(14)(15)(16) based on which we can suppose that, to respond to the demand concerning the amount of information, the quality of the information provided should be taken into account, as many variables interfere in the absorption of the information, such as the patient's way of life, the patient and family's ability to understand the information and how they interpret the disease.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although some questions were answered satisfactorily, showing scores far superior to the average, it was observed that 89% of the sample indicates the desire to receive more overall information. This finding is very close to the results presented in other studies, (12)(13)(14)(15)(16) based on which we can suppose that, to respond to the demand concerning the amount of information, the quality of the information provided should be taken into account, as many variables interfere in the absorption of the information, such as the patient's way of life, the patient and family's ability to understand the information and how they interpret the disease.…”
Section: Discussionsupporting
confidence: 93%
“…We believe that this is related to the fact that the sample consists of patients hospitalized at a surgical ward, which means more medical tests and therapeutic conducts, consequently offering information about the test objectives and results and about the disease and treatment more constantly. This finding is similar to the observations by Adler et al, (12) in which the same questionnaire was applied to 72 patients and participants in the German study and to the phase IV study concerning the validation of the EORTC QLQ-INFO25 by Arraras et al (6) Almost all participants indicated some knowledge about the diagnosis of their oncologic disease. About 89% of the sample referred having received moderate or plenty of information.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Es drohen Versorgungsbrüche, die einer optimalen Nachversorgung durch eine zeitnahe Reaktion auf Therapie-oder Krankheits-bedingte Beeinträchtigungen der Lebensqualität entgegenstehen. Aus eigenen Untersuchungen wissen wir außerdem, dass viele Patienten trotz intensiver Behandlung zu wenig über Selbstmanagement-Möglichkeiten, Therapieinhalte, die langfristige Behandlungsplanung oder den Sitz zuständiger Spezialisten wissen [14]. Auch auf Seiten der Professionals (Ärzte, Pflegende, Medizinische Fachangestellte, Sozialarbeiter) führt die zunehmende Komplexität der Versorgung onkologischer Patienten im Multimodal cancer treatment gelegentlich zu Unterversorgung, medizinischen Fehlentscheidungen, Doppeluntersuchungen, unnötigen Wartezeiten für die Patienten oder Versorgungsbrüchen [6,15].…”
Section: Hintergrundunclassified
“…Our survey results confirm findings from studies asking patients with various malignancies to respond to the EORTC QLQ-INFO25. 4,5 In these studies it was shown that patients received more information about medical tests, disease and treatment than about other services, different places of care and self-help.…”
mentioning
confidence: 99%